Statistical Characteristics of Convective Clouds over the Western Ghats Derived from Weather Radar Observations. Issue 18 (30th September 2017) - Utsav, Bhowmik; Deshpande, Sachin M.; Das, Subrata K.; Pandithurai, Govindan
Abstract: X‐band radar observations at Mandhardev (18.04°N, 73.85°E) are used to investigate statistics of convective clouds over the Western Ghats during monsoon season (June–September 2014). Convective storms (cells) are identified using an objective‐tracking method to examine their spatiotemporal variability, thus quantifying the time‐continuous aspects of convective cloud population over the region for the first time. An increased frequency of storm location and initiation along the windward mountains compared to coastal and lee side highlights orographic response to southwesterly flow, with superimposed diurnal cycle. An eastward progression of convective activity from upstream the barrier through windward slopes of mountains over to the lee side is observed. Storm area, height, and duration follow lognormal distributions; wherein, small‐sized storms contribute more to total population and unimodal distribution of 35 dBZ top heights (peaking at 5.5 km) depicts the dominance of shallow convection. Storms exhibit a pronounced diurnal cycle with a peak in afternoon hours, while the convective area maximum is delayed by several hours to that of precipitation flux. Cell lifetime and propagation show that cells move with slow speeds and have mean duration of 46 min. They align east‐west nearly parallel to mountain ridges, and their direction of movement is steered mostly by large‐scale winds at lower levels. Based on top heights, convective cells are further classified into cumulus, congestus, and deep clouds. In general, congestus (deep) cells are most abundant in the windward (leeward) side. A lead‐lag relationship between congestus and deep cells indicates midtroposphere moistening by congestus cells prior to deep convection. Key Points: Spatial distribution of convective storms highlights effect of orography on convection initiation Convective storm properties (area, height, and duration) follow lognormal frequency distribution Overall, shallow convection dominates the region and persists for an average duration of 46 min